Phenotype of plasma cells in multiple myeloma and monoclonal gammopathy of undetermined significance - Kovarova, L; Buresova, I; Buchler, T; Suska, R; Pour, L; Zahradova, L; Penka, M; Hajek, R (Neoplasma, 2009)
Flow cytometry is a useful tool for the analysis of plasma cells in monoclonal gammopathies. The aim of this study was to find possibilities and limits of multicolour flow cytometry in diagnostics of monoclonal gammopathy of undetermined significance (MGUS) and multiple myeloma (MM) and to identify parameters that could be used to differentiate between these two disorders. Surface markers CD38 and CD138 were used for identification of plasma cells, CD19 and CD56 further distinguished normal and abnormal plasma cells, respectively. The percentage of circulating plasma cells in peripheral blood was lower in MGUS patients then in MM (p<0,001) In bone marrow, the percentage of residual polyclonal CD19 plasma cell was higher (p<0,001) and the percentage of malignant monoclonal CD56 plasma cell was lower (p<0,001) in MGUS than in MM. In conclusion, flow cytometry is relatively quick and effective method for analysis of plasma cells thus immunophenotyping can significantly contribute to the differential diagnosis of plasma cell proliferations.
Keywords: Humans; lidé středního věku; antigeny CD38; Paraproteinemias; Multiple Myeloma; Female; Aged; dospělí; antigen CD56; Phenotype; senioři; lidé; plazmatické buňky; syndekan-1; Antigens, CD19; Plasma Cells; mnohočetný myelom; Adult; ženské pohlaví; Male; Flow Cytometry; Middle Aged; paraproteinemie; fenotyp; antigeny CD19; prognóza; Aged, 80 and over; CD56 Antigen; senioři nad 80 let; průtoková cytometrie; ADP-ribosyl Cyclase 1; mužské pohlaví; Prognosis; Syndecan-1